Superparamagnetically modified A-type, X-type and CHA-type zeolites with silica-coated Fe3O4 and CoFe2O4 nanoparticles for removal of Sr2+ and Cs+ from radioactively contaminated water - Ito, Azusa; Thirunavukkarasu, Gnanavel; Hriljac, Joseph A. (Frontiers in Environmental Chemistry, 2024)
Magnetised zeolite A, zeolite X and Na,K-CHA composites with superparamagnetic nanoparticles of SiO 2 -coated Fe 3 O 4 or CoFe 2 O 4 ferrite spinels were prepared, characterised and tested for ion exchange efficacy. They were synthesised by following three steps, synthesising Fe 3 O 4 and CoFe 2 O 4 nanoparticles by a solvothermal method, coating the metal oxide particles with SiO 2 by a sol-gel process, and attaching the M x O y /SiO 2 onto the zeolites during synthesis. The magnetic zeolites were characterised by X-ray diffraction, X-ray fluorescence spectroscopy, Raman spectroscopy, vibrating sample magnetometry and both scanning and transmission electron microscopy. It was confirmed they had superparamagnetic properties due to successful attachment of the M x O y /SiO 2 particles onto the zeolites. Adsorption capacities of Sr 2+ onto the magnetic zeolite A and zeolite X and Cs + onto the magnetic Na,K-CHA were also evaluated. The results show the M x O y /SiO 2 did not block the adsorption sites of the zeolites and the M x O y /SiO 2 particles were not detached from the zeolites during the adsorption experiments.